Under pressure: non-medical use of prescription drugs among undergraduate students - Demenech,Lauro Miranda (2020)
ABSTRACT Objective To measure lifetime, last-year and last-month prevalence of Non-Medical Use of Prescription Drugs (NMUPD) as well as the characteristics associated to last-month NMUPD among undergraduate students of a university in southern Brazil. Methods This was a cross-sectional study, with a sample that was selected through a clustered systematic sampling strategy. Multivariate analysis was conducted with Poisson regression according to a four-level hierarchical model of analysis. Fieldwork was conducted in 2015, and 1,423 students participated. Results Lifetime, last-year and last-month prevalence of NMUPD were 25.2%, 13.1% and 8.5%, respectively. Anxiolytics and barbiturates were the most prevalent. Variables independently associated were being female, having a family income lower than one or higher than six Brazilian minimum wages, being enrolled in a health sciences-related undergraduate course, and having reported lifetime NMUPD by a friend. Conclusions Based on these results, we suggest the development of prevention and promotion activities on this theme for students and professors, especially among those from health sciences-related courses. These interventions should focus on harmful effects of NMUPD, psychosocial coping strategies and socially established gender roles.